FISHBONE ANALYSIS METHOD OF COMMUNICATION HANDOVER IN THE EMERGENCY INSTALLATION IN JAKARTA ARMY HOSPITAL: DOI: https://doi.org/10.35654/ijnhs.v1i2.40 - Deny Gunawan; Rr Tutik Sri Hariyati; Desnita Fitri (Alta Dharma Publisher, 2018)
Background: The handover and transfer of identification often experience a weakness in its implementation and become global problems at the hospital.Objective: This paper focuses on the cause of less optimal implementation of Identification Situation Background Assessment Recommendation (ISBAR) method when conducting handover of nurses among shifts at Army Hospital in Jakarta. Methods: This study employed situation study analysis with a fishbone diagram approach that includes 5M and 1E.Literature review and analysis were utilized to produce recommendation for improving the quality of the ISBAR method implementation when conducting handover of nurses among shifts. Data were obtained from the existing-secondary data, previous research data and data sources from Jakarta Military Hospitals. Results: Data were analyzed using fishbone, data obtained for the cause was not optimal ISBAR method when nursing handover between shifts. causes the problems identified can be prioritized are no tools monitoring evaluation, there is no definitive monitoring evaluation team, monitoring evaluation implementation of nurse handover within shift, hospital has not been a paperback book about ISBAR, components in the handover format not optimal, and the nurse has not been understood properly ISBAR method. Conclusion: The research result reveals six causes of the problem. They are: (1) the absence of evaluation monitoring tools, (2) the absence of definite evaluation monitoring team, (3) non optimal handover evaluation monitoring of nurses among shifts,(4) the absence of a pocket book on ISBAR delivery method, (5) non optimal components in the handover format, and (6) nurses’ inability to conduct ISBAR method correctly.Recommendation: propose the ISBAR method of monitoring and evaluating the handover of nurses between shifts, the establishment of an ISBAR method evaluation monitoring team to hand over nurses between shifts, a draft evaluation monitoring tool, making a pocket book about the ISBAR method, the ISBAR component in the nurse handover format, and provide education and roleplay of the ISBAR method when handover of nurses between shifts